Pelatihan Pembuatan Media LKS Interaktif Berbantuan Aplikasi Wizer.Me Untuk Guru-Guru SMP di Pondok Pesantren Modern Al-Muqoddas - Hamidah, Ida; Sadikin, Hasan (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2024)
Based on the results of observations, it was found that some teachers were still not proficient in compiling application-based learning tools for online learning. Some teachers are also still not familiar with various types of practical applications that can be used in learning, including the use of the wizer.me application. The wizer.me application is an interactive and interesting online LKS creation site. The ability to create interactive IT-based media is very important for teachers, especially during the current pandemic. The purpose of this training is to improve the ability of teachers to develop interactive learning tools based on wizer.me and implement them in learning in their respective classes. The method used in the implementation of this training is a descriptive method. The steps taken in the implementation of this training include (1) socialization, (2) initial observations (in the form of open interviews), (3) implementation (interactive media creation training seminars), (4) checking learning tools and simulations (samples). resource modeling, (5) Final evaluation. The results of this study indicate an increase in the ability of teachers to develop interactive learning tools based on wizer.me and implement them in classroom learning.